Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.3329/bjas.v45i1.27485
|View full text |Cite
|
Sign up to set email alerts
|

In vitro production of bovine blastocyst with oocyte collected from abattoir ovary

Abstract: This study was designed to adopt in vitro embryo production (IVP) protocol using abattoir ovary. Ovaries were collected from local abattoir; cumulus-oocyte-complexes (COCs) were aspirated from 3 to 8 mm diameter follicles using a 10 ml disposable syringe attached with a 21G needle. The COCs were selected based on morphological characteristics and selected COCs were transferred into in vitro maturation (IVM) medium for 22 to 24 hrs. The matured COC were fertilized in vitro (IVF) using fresh semen capacitated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 0 publications
2
8
0
Order By: Relevance
“…The lowest percentage of maturation was in M-I stage. This result supported by Vivian et al (2018) who reported the average nuclear maturation in bovine was 58.2%, and lower than Deb et al (2016) who reported 74.16% as detected by extrusion of first polar body and Gabr et al (2015) who reported 67% in TCM -199 medium. However this result was higher than Saleh (2017) who reported 45% by aspiration, 31% in slicing and 32% in aspiration plus slicing.…”
Section: The Effect Of Collection Technique On Ivmsupporting
confidence: 82%
“…The lowest percentage of maturation was in M-I stage. This result supported by Vivian et al (2018) who reported the average nuclear maturation in bovine was 58.2%, and lower than Deb et al (2016) who reported 74.16% as detected by extrusion of first polar body and Gabr et al (2015) who reported 67% in TCM -199 medium. However this result was higher than Saleh (2017) who reported 45% by aspiration, 31% in slicing and 32% in aspiration plus slicing.…”
Section: The Effect Of Collection Technique On Ivmsupporting
confidence: 82%
“…There is a discrepancy in the reproductive performance between different cattle breeds. Using abattoir-derived ovaries and data base information we studied the effects of breed on in vitro fertilization and early embryo development (4).…”
mentioning
confidence: 99%
“…The current oocyte collection followed by their in vitro maturation, in vitro fertilization, in vitro culture and embryo transfer to recipient have improved much to support commercial application of the IVP. Bangladesh Livestock Research Institute (BLRI) has also adopted IVP technology (Deb et al, 2016). The present study reported embryonic development rates to cleavage and to blastocyst stage at BLRI are 75.5±2.7% and 16.6±3.9% respectively.…”
Section: Discussionmentioning
confidence: 63%
“…However, cleavage and blastocyst development rate is little improved than our previous report (Deb et al, 2016). Several factors including oocyte donor, oocytes handling, semen quality, culture media, culture conditions, osmolality of media, CO 2 level of incubator and water quality used for glassware cleaning, media preparation and others steps of IVP influences the rate of blastocyst development (Fukuda et al, 1987, Gordon, 1994, Brum et al, 2005.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation